Common mistakes in writing basic elements of C++ programming for dummies / Syarifah Adilah Mohamed Yusoff, Rozita Kadar and Saiful Nizam Warris - Mohamed Yusoff, Syarifah Adilah; Kadar, Rozita; Warris, Saiful Nizam (Unit Penerbitan JSKM, 2020)
“Understanding that in the future there is no profession is untouched by machines means admitting that coding is part of the liberal arts” according to Wall Street Journal (2015). Therefore, giving basic education on programming language to primary and secondary school is one of strategic planning in Education 5.0. Not every child learn writing will become a novelist, nor everyone who learn algebra a mathematician, yet we treat both as foundation skills for all children. Coding is the same since the future consist of emerging industries of cryptocurrency and Artificial Intelligence space. Coding is uniquely suited to training children not just how to solve problems, but also how to express themselves (Resnick, 2019). Introduction to programming language has been taught to several programmes in university level. In Universiti Teknologi MARA Cawangan Pulau Pinang, Malaysia, engineering students for both diploma and degree levels are compulsory to enrol the course. The necessity of taking this course lies on practising problem solving skills, expose students to writing programming language and simulate creative thinking in solving problems. All of the students are categories as novice programmers due to has no official learning both in programming and computer essential. Hence, learning computer language is not only new but difficult to understand the rules and structures. The next sections will discuss about common mistakes in basic elements of programming and input and output statements respectively.